Diagnosis of 5α-reductase type 2 deficiency: Contribution of anti-Müllerian hormone evaluation - Stuchi-Perez, Eliana G.; Hackel, Christine; Oliveira, Luiz Eduardo C.; Ferraz, Lucio F. C.; Oliveira, Laurione C.; Nunes-Silva, Daniela; Toralles, Maria Betania; Steinmetz, Leandra; Damiani, Durval; Maciel-Guerra, Andrea T.; Guerra Júnior, Gil (De Gruyter, 2005)
Aim: To evaluate anti-Müllerian hormone (AMH) levels in patients with clinical and molecular diagnosis of 5α-reductase 2 deficiency. Patients and methods: Data from 14 patients whose age ranged from 21 days to 29 years were analyzed according to age and pubertal stage. Sexual ambiguity was rated as Prader III in 11 patients. LH, FSH, testosterone (T), dihydrotestosterone (DHT) and AMH serum levels were measured in all but two patients, who had been previously submitted to gonadectomy; T and DHT were also measured in 20 age-matched controls. Results: Gonadotropin levels were normal in all but one patient who retained gonads (six of whom had reached puberty) and T/DHT ratio was elevated in all patients when compared to controls. All prepubertal patients had AMH levels < -1 SD for age, while most pubertal patients had AMH levels compatible with pubertal stage. Conclusions: Prepubertal patients with 5α-reductase 2 deficiency have AMH values in the lower part of the normal range. These data indicate that T does not need to be converted to DHT to inhibit AMH secretion by Sertoli cells. © Freund Publishing House Ltd., London.
Keywords: 5α-reductase; Androgen insensitivity syndrome; Dihydrotestosterone; Müllerian inhibiting hormone; Pseudohermaphroditism; Testosterone; androstanolone; glycoprotein; mullerian inhibiting hormone; mullerian-inhibiting hormone; steroid 5alpha reductase; testis peptide hormone; testosterone; androgen receptor; chorionic gonadotropin; follitropin; luteinizing hormone; Muellerian inhibiting factor; adolescent; adult; blood; case control study; child; female; genetics; human; infant; male; newborn; orchiectomy; physiology; preschool child; age distribution; clinical article; controlled study; gonadectomy; gonadotropin blood level; hormonal regulation; hormone action; hormone blood level; hormone determination; hormone release; prepuberty; protein deficiency; pseudohermaphroditism; puberty; sexual dysfunction; testosterone blood level; type 2 5alpha reductase deficiency; Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Female; Glycoproteins; Humans; Infant; Infant, Newborn; Male; Orchiectomy; Testicular Hormones; Testosterone 5-alpha-Reductase